Evaluation of Various Permanent Magnet Arrangements on Linear Actuator - Abdul Shukor, Fairul Azhar; Misron, Norhisam; Wakiwaka, Hiroyuki; Tashiro, Kunihisa; Nirei, Masami (2012)
Linear actuator is use to provide linear motion with absence of motion translator. By using the linear actuator, the linear motion could be produce with high degree of efficiency. Slot less type and slot type are two type of linear actuator. Apart being either slot less type or slot type of it stator, there are various of magnetization arrangement can be apply on it mover. In this paper, there are 10 different of magnetization arrangements were used to evaluate the slot less type and slot type of linear actuator. There are 9 different performance characteristics were used to find the best structure of linear actuator. As a result, it is shown that, the slot less type of linear actuator generally have a better dynamic performance, while the slot type of linear actuator having a better static performance. There are 4 different structure of linear actuator with different of magnetization arrangement was selected as the best model of linear actuator.